The effect of multi-micronutrient and protein supplementation on iron and micronutrients status in pregnant women (Faculty of Medicine Universitas Indonesia, 2015)
Background: Potential benefits of multiple micronutrient supplements has become an increasing interest seeing as the high rate of pregnant women with suboptimal nutritional status, but low compliance often reduces effectiveness of large-scale iron and folic acid supplementation program. The aim of this study was to investigate the efficacy of multi-micronutrient and protein supplementation on iron and micronutrients status in pregnant women. Methods: An exploratory study was conducted to 100 pregnant women ≤ 12 weeks, who underwent antenatal care in Budi Kemuliaan Hospital, Jakarta. The subjects received formulated powder milk containing multi-micronutrient and protein supplement monthly until delivery. Anthropometric measurement, maternal and cord blood exam, ultrasound and dietary recall were done. The data was analyzed by correlation test. Correlation between variables was tested using Pearson or Spearman correlation test. Results: The mean maternal hemoglobin level significantly decreased during study (p < 0.001), being the lowest in second trimester. The levels on the first, second, and third trimester respectively was 12.16 ± 1.03 g/d; 12 anemic subjects and 17 had low ferritin level, 10.85 ± 0.95 g/dL; 58 anemic subjects and 69 had low ferritin level, and 11.02 ± 0.35 g/dL; 50 anemic subjects and 51 had low level of ferritin). Ferritin and serum iron levels were decreased at trimester one and two (p < 0.001), also the zinc and vitamin D level declined. Anemia did not correlate with pregnancy outcomes such as preterm delivery, preeclampsia, or low birth weight. Conclusion: The levels of maternal hemoglobin, ferritin, iron, zinc, and vitamin D during pregnancy could not be maintained or increased by multi-micronutrient and protein supplementation.